Tracking Results in Agriculture and Rural Development in Less-Than-Ideal Conditions : A Sourcebook of Indicators for Monitoring and Evaluation - Larson, Gunnar (World Bank, Washington, DC, 2012)
The demand for verifiable evidence of results and impacts of development agricultural programs and projects is growing. However, most of the indicators that development practitioners have traditionally used in tracking progress toward achieving projects' objectives focus on the workings of the development operation itself. These performance indicators relate mainly to lower-level inputs and outputs and are used to populate management information systems. Higher-level indicators are used to measure progress in achieving the ultimate objectives of projects, and in bringing about larger outcomes and impacts. The ability to measure and demonstrate outcomes and impacts relies on the use of indicators that are based on reliable data and on the capacity to systematically collect and analyze that information. The conditions in which monitoring and evaluation (M&E) are carried out vary widely, depending on the demand for information, the extent to which it is used to inform decision-making, and the reliability of the systems that are in place to capture and convey that information. Throughout much of the developing world these conditions are "less-than-ideal," and information is irregular and often lacking altogether. In these conditions there is a lack of effective demand for information on the part of policy makers. The conditions are often especially pronounced for data related to rural areas, where the costs of data collection are high and the quality of existing data is particularly low. Building data systems and developing and supporting capacity for M&E in these conditions is, therefore, a pressing imperative for interventions in the agriculture and rural development sector. Strengthening capacity for M&E begins at the national and sub-national levels, where addressing the weaknesses of national statistical systems is a common priority. The data collected and reported within countries must not only be of sufficient quality to inform planning and policy formulation but must also be consistent between countries.